Condensed tannins: A factor limiting the use of cassava forage - Reed, J.D.; McDowell, R.E.; Soest, P.J. van; Horvath, P.J. (Wiley, 1982)
A study conducted to determine factors influencing the nutritional value of cassava forage other than cyanogenic glycosides; presents the results of a fiber analysis that reveals the presence of condensed tannins in the neutral-detergent fiber of cassava leave blades; also presents data on the composition and in-vitro digestibility of leaf blade, petiole, stem and whole leaf, as well as the amount of insoluble pepsin and protease in six varieties of cassava.